Lessons from early central banking for today - Ulrich Bindseil (IBF - Institut für Bank- und Finanzgeschichte, 2021)
Contrary to popular belief, the history of central banking begins much earlier than 1800. Many current issues of central bank policy can be traced back to the public giro banks of the 15th century, and have been discussed in numerous essays at least since the 17th century. Are the same debates merely repeating themselves in new shapes? And, more importantly, what can we learn today from those first four centuries of central bank history and debates? This paper argues that despite the end of convertibility into precious metal of central bank money, relevant lessons can be derived from early central banking for today, and develops this around five concrete themes.
Keywords: E5; N2; 330; Zentralbank; Geldpolitik; Krisenmanagement; USA